THE BUBBLE OF ILLUSORY GROWTH “THE CASE OF THE IRAQI ECONOMY” - Assistant professor: Arshad Abdul Lateef Turki (Scholars Digest Publishing, 2024)
Real, material economic growth” is defined as the process of increase in real income, an increase of a continuous, cumulative nature over a specific period of approximately (a quarter of a century) “as this increase exceeds the rate of population growth while providing various vital productive and social services and preserving renewable resources from the risk of environmental pollution and depletion.” " “The problem of almost complete dependence on oil revenues in building economic policy,” in a reality in which the contribution of oil revenues to the general budget reaches more than 90% and approximately 60% of GDP, while the topic of real economic growth occupies great importance in economic and financial literature because it is considered a factor. True to the economic reality and the extent of economic prosperity witnessed by the country. The researcher assumes, material economic growth is adopted as it is possible for the oil sector to become a growth engine that contributes to the diversification of the Iraqi economy by involving all productive sectors in economic development. “The researcher reached several fundamental results, which is the difficulty of achieving real economic growth.” materialistic reliance on oil rents only. Therefore, it is necessary to activate the idle real productive sectors, and also by taking a specific period from 2015-2022. The oil rentier syndrome for economic growth became clear through the link between public revenues and oil sales and then the accumulation of cash reserves.
Keywords: Imaginary economic growth - public revenues - real material economic growth - oil revenues - World Bank - oil sector - real sectors.